UTILIZATION OF PRAWN WASTE-ISOLATION OF CHITIN AND ITS CONVERSION TO CHITOSAN - MADHAVAN, P; RAMACHANDRAN NAIR, K G (Fishery Technology, 2017)
A process is described for the preparation of chitosan fromprawn waste. The process involves extraction of protein using0.5% sodium hydroxide solution, bleaching the protein freemass with bleach liquor containing 0.3-0.5% available chlorinefollowed by demineralisation with 1.25 N hydrochloric acid inthe cold and deacetyiation using 1:1 (w jw) sodium hydroxidesolution at 100Â°C for 2 hours.